Dispositional coping, coping effectiveness, and cognitive social maturity among adolescent athletes - Nicholls, A. R.; Perry, J. L.; Jones, L.; Morley, D.; Carson, F. (Journal of Sport & Exercise Psychology, 2013)
It is accepted among scholars that coping changes as people mature during adolescence, but little is known about the relationship between maturity and coping. The purpose of this paper was to assess a model, which included dispositional coping, coping effectiveness, and cognitive social maturity. We predicted that cognitive social maturity would have a direct effect on coping effectiveness, and also an indirect impact via dispositional coping. Two hundred forty-five adolescent athletes completed measures of dispositional coping, coping effectiveness, and cognitive social maturity, which has three dimensions: conscientiousness, peer influence on behavior, and rule following. Using structural equation modeling, we found support for our model, suggesting that coping is related to cognitive social maturity. This information can be used to influence the content of coping interventions for adolescents of different maturational levels.